(untitled) (Al-Academy, 2015)
The current study discusses one of the most important modern schools in art, and it studies its impact on contemporary Iraqi art, particularly in the art of pottery because of its association to the utilitarian function. However, this study demonstrated that pottery is a unique art, which has exceeded the limits of this function. In addition, pottery has a great role in changing the view and understanding of it. Therefore, this art assists in achieving the concepts, philosophies, and values among other fine arts branches.The most prominent issues in this article is dealing with reflections of the cubical arts on the Iraqi contemporary pottery art by through the works of the most prominent contemporary artists such as (Saad Shakir, SHaniar Abdullah and Tariq Ibrahim). They are the finest potters who have been and continue to have a clear imprint in the history of contemporary Iraqi art.Cubism art is not a spur of the moment in Mesopotamia, but it has a long history and deep roots stretch since the time of our ancestors, the Sumerians, where the imprint is clear in this field. The researcher has present a model of the ceramic works of the Sumerians as this civilization replete with artistic and aesthetic achievements that we are proud of as an Iraqis and as a part of this legacy. Accordingly, it is not surprising when contemporary potters repeat the achievements of their ancestors but in contemporary and modern styles. It is continuing message passing from generation to a generation but in different methods. The first chapter discusses the research problem, importance and the aims of the study, boundaries, and determines the terms such as the ‘cubism’. Chapter two consist of two main topics, the first is (Introduction to Cubism), the second is (the cubical trend in the contemporary Iraqi pottery art). Chapter three included the procedures and methodology used and the research, community and the selection of the research sample, and then the sample’s analysis. The fourth chapter represents the most important conclusions such as: The results shows that the artwork produced by the potters (SaadShakir and Haniar Abdullah Tariq Ibrahim) have contemporary and geometric cubical style in its theme. They have done this in deliberately manner to give the regularity and harmony as a specific feature of each of them. The results also show that all the artworks have an existence of a common factors in terms of the external configuration, but they are differ in the idea and the extent of their impact in the delivery to the receiver, where the artwork consists of a social, utilitarian and/or aesthetic functions. In the end, I have listed the recommendations and a list of resources.